DAKWAH DAN JURNALISTIK ISLAM (Perspektif Dakwah Islamiyah) - Ramli Ramli (KOMUNIDA : Media Komunikasi dan Dakwah, 2015)
Da'wah is the Islamic message to mankind, and an obligation for every Muslim, because the Qur’an that states perform religious orders and demand / develop a science that in principle also told to study writing, sent preaching through writing (print media) or through Islamic journalism. That which is one form of media utilization, namely the media as a series of papers from all the elements of mission as a whole that can not be separated in order to achieve mission objectives, namely the implementation of Islamic da’wah for all mankind. Islamic journalistic activity is an activity to collect, prepare, write, and disseminate information through mass media. In particular information about the teachings of the Qur’an and the Sunnah of the Prophet. So it becomes an Islamic journalistic activities and are not contrary to norms and ethics in the teachings of Islam. in order to reach goals of the mission can be easily accepted by society